INDONESIA’S CONTRIBUTION OF DISPATCH THE NATIONAL POLICE AS A PEACEKEEPING OPERATIONS IN THE CENTRAL AFRICAN REPUBLIC IN 2019 - Faudina, Tasya; Nurhadi, Robi (Universitas Nasional, 2022)
This study expects to depict and dissect the job of Indonesia's investment in MINUSCA in the 2019 period. Where, Indonesia is in the main ten as a shipper of Peacekeeping soldiers and police. Thus, in this study there is a research question in the form of